Pelatihan Kepenyiaran dan Sosialisasi melalui Program Acara “Ngobrol Pintar (Ngopi)” di Radio Basuma FM - Irawan Suprapto; Rosy Febriani Daud (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2022)
The broadcasting field is growing rapidly according to the level of human civilization which is increasingly advancing with advances in communication technology. Radio is one of the electronic media for distributing information and forming communication and public opinion which has a very strategic role. In its development, radio has become a communicative, educative and entertaining medium, which only requires the sense of hearing so that it can be heard anywhere. As an electronic mass media, a lot of information about the social condition of North Lampung district and entertainment is packaged into a